Maillard Reaction in Natural Rubber Latex: Characterization and Physical Properties of Solid Natural Rubber - S. Montha; P. Suwandittakul; A. Poonsrisawat; P. Oungeun; C. Kongkaew (Advances in Materials Science and Engineering)
Maillard reaction in Natural Rubber (NR) latex was investigated by treating fresh NR latex with glutaraldehyde (C5H8O2) in amounts of 0, 50, 100, and 200 mmol/kg of latex. Protein cross-linking in fresh NR latex and solid NR was confirmed by using sodium dodecylsulfate polyacrylamide gel electrophoresis (SDS-PAGE) and attenuated total reflection infrared (ATR-IR) spectroscopy, respectively. It was found that degree of protein cross-linking in NR increased with increasing C5H8O2 concentration. Physical properties of untreated and treated NR substances in terms of gel content, initial Wallace plasticity (P0), plasticity retention index (PRI), Mooney viscosity, and tensile strength were carefully explored. Results clearly showed that the Maillard cross-linking of proteins had remarkable effect on bulk NR properties, that is, solvent resistance, hardness, resistance to oxidation, rheological behavior, and resistance to stretching out.